The Role of Black Soybean and Purple Sweet Potato Active Compound on Advanced Glycation End-Product in Streptozotocin-Induced Type 2 Diabetes Mellitus Rat - Gofur, Abdul; Arifah, Siti Nur; Annisa, Yuslinda; Witjoro, Agung; Atho'illah, Mochammad Fitri; Lestari, Sri Rahayu (Journal of Tropical Life Science, 2019)
Diabetic nephropathy is one of the diabetes complications attacking kidney leading to kidney damage. Hyperglycemia accompanying DM causes the increase of Ad-vanced Glycation End-Product (AGE) and Receptor Advanced Glycation End-Product (RAGE) activity, then develop kidney damage and other diabetes compli-cations. The study aimed to investigate the effect of black soybean, purple sweet potato, or their combination on the expression of AGE, RAGE, and kidney necro-sis T2DM model rats. The rats were given with high-calorie diet for five weeks and then injected with a low dose of streptozotocin (30 m/kg Body Weight) in intraperitoneal. DM rats were divided into: normal, K- (T2DM), K+ (T2DM + glibenclamide 0.6 mg/kg body weight), P1 (T2DM + black soybean), P2 (T2DM + purple sweet potato), and P3-5 Combination 1-3 (T2DM + combination of black soybean and purple sweet potato in ratio of 1 : 3, 2 : 2, and 3 : 1). DM rats were then given the treatments for thirty days. The effect of black soybean, purple sweet potato, or the combination of both was evaluated through the expression of AGE, RAGE, and necrosis of renal tubules. The changes in renal tubules histological characteristics were evaluated using hematoxylin-eosin (HE) staining. Immuno-histochemistry analysis of renal tubules was to evaluate AGE-RAGE expression after the treatments. The research results indicated that there was a significant dif-ference from the combination of black soybean and purple sweet potato in reduc-ing AGE, RAGE, and renal tubules necrosis. The BSB and PSP combination ratio of 1:1 was able to improve renal tubules, decrease the expression of AGE and RAGE towards near normal. The combination of black soybean and purple sweet potato could be used as one of the alternatives to improve kidney damage in dia-betic nephropathy.